PELAKSANAAN GAME BASED LEARNING PADA SISWA KELAS IV SD NEGERI 091254 BATU ONOM POKOK BAHASAN DAUR AIR DAN PERISTIWA ALAM UNTUK MENINGKATKAN ASPEK KOGNITIF - Simanjuntak, Melvin; Nenny Wati Harianja; Eva Sorti Sihombing; Dani Sitopu; Sando Putra Haloho; Castri Veronika Sitopu; Santi Dorama Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on initial observations, the science learning process at SD N 091254 Batu Onom for the 2024 academic year is not yet optimal. This is proven by the grade IV odd semester report cards with an average score of 69.5. This classroom action research was carried out by applying the Game Based Learning model. The Game Based Learning Model is a learning model with a play approach. The play method in learning functions to increase enjoyment and eliminate student boredom while studying so that it can increase students' enthusiasm for learning. This research aims to find out whether this method can improve students' cognitive aspects. This classroom action research consisted of 2 cycles with the research subjects being 23 students in class IV of SD N 091254 Batu Onom. Data about cognitive aspects was obtained from student test results. Indicators of success in the cognitive aspect must achieve a minimum of 65% completeness from at least 85% of the number of students taking the test. The research results showed an increase in students' cognitive aspects from cycles I to II. The cognitive aspect of cycle I during the pre test was 19.5% to 39.5% during the post test and cycle II during the pre test was 38% to 97.6% during the post test. This learning model can be successful because the question disc game system requires students to answer questions randomly, so that students are responsible for their own answers and knowledge. From the research results, it can be concluded that the application of the Game Based Learning model on the subject of the water cycle and natural events can improve the cognitive aspects of fifth grade students at SD N 091254 Batu Onom.